What your fifth grader needs to know : fundamentals of a good fifth-grade education - Hirsch, E. D., Jr. (Eric Donald), 1928- (New York, N.Y. : Delta Trade Paperbacks, 1995)
Shows parents what thier fifth grader needs to know in order to make progress in school and be effective in society.
I. Language arts. Stories and speeches ; A few poems for fifth grade : The living world ; Humor ; American themes ; Feelings and ideas ; Learning about language ; Learning about literature -- Sayings and phrases -- II. Geography, world civilization, and American civilization. Geography of the United States and the world ; Geography ; World civilization ; American civilization -- III. Fine arts. Music ; Visual arts -- IV. Mathematics. Whole numbers ; Decimals-- addition, subtraction, and multiplication ; Division ; Decimal division ; Fractions ; Measurement ; Plane figures ; Area ; Ratio, scale, percent, average, graphs ; Rectangular prisms and cubes ; Volume; Rates and speed ; Functions and equations -- V. Natural sciences. Life sciences ; Physical sciences ; Mechanical concepts ; Transferring heat energy ; Electricity ; Motion, engines, and motors ; Stories of scientists.
Originally published: New York : Doubleday, c1993.
Includes index.
Keywords: Fifth grade (Education) -- Curricula -- United States; Curriculum planning -- United States